PENGARUH KOMITMEN PROFESIONAL, TIPE KEPRIBADIAN, GENDER TERHADAP KEPUASAN KERJA AKUNTAN PUBLIK - Sri Iswati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
The objective of the research is to test professional commitment affects to the job satisfaction of public accountant by means of the personality and gender as moderator variables. This is a quantitative research that uses multiply regression analysis. Primary data are gathered through questionnaires and executed by reliability and validity test.And the results show that the six hypotheses have proved significantly: (1) the professional commitment affect the job satisfaction; (2) personalit affect to the job satisfaction; (3) the gender do not affect to the job satisfaction; (4) the interaction between professional commitment and personality affect the job satisfaction; (5) the interaction between professional commitment and gender affect to the job satisfaction; and (6) all variables affect to the job satisfaction of  public accountant.Key words:  Professional commitment, personality, gender, job satisfaction, and public accounntant